2021
DOI: 10.1111/jcpt.13562
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a decision support system on the incidence of prescription errors in a PICU

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The fact that handwritten prescriptions contained more errors than electronic prescriptions is a plausible nding, as CPOE leads to standardized, legible, and complete prescriptions [31].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that handwritten prescriptions contained more errors than electronic prescriptions is a plausible nding, as CPOE leads to standardized, legible, and complete prescriptions [31].…”
Section: Discussionmentioning
confidence: 99%
“…In other settings it has previously been shown that CDSS can decrease prescribing errors and wrong doses in children [ 27 , 28 ]. Little is known about the effects of using a CDSS for this population in community pharmacies.…”
Section: Discussionmentioning
confidence: 99%
“…Community pharmacists have an important role in preventing DRPs in pediatric patients [ 24 ], but studies indicate that more training or better support is needed for pharmacists to be able to detect and prevent errors in this population [ 25 , 26 ]. Furthermore, there is limited knowledge about CDSS to prevent DRPs in pediatric patients in the community pharmacy setting [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lacking effect of CPOE on dosing errors was also seen by Roumeliotis et al [ 28 ]. Dosing errors could be prevented more effectively by a fully integrated CDS that offers dosing support and automated dose check [ 31 ].…”
Section: Discussionmentioning
confidence: 99%